Five-year Follow-up of Ocular Deviation in Bilaterally Pseudophakic Patients. (June 2013) - Hoshikawa, Rie; Ito, Misae; Shimizu, Kimiya; Ishikawa, Hitoshi; Amano, Rie
ABSTRACT Purpose: To investigate long-term ocular deviation in patients who had undergone implantation of a monofocal intraocular lens (IOL) in both eyes. Methods: Eighty-eight patients with exophoria (average age, 68 ± 8 years; average axial length, 23.9 ± 0.9 mm) scheduled for bilateral phacoemulsification and monofocal IOL implantation were recruited. Before surgery and at 1, 3, and 6 months and 1, 2, 3, 4, and 5 years after surgery, we assessed ocular deviation near stereopsis in patients wearing their normal spectacles. Results: At 5 years after surgery, near stereopsis had a median value of 50 arcsec and the mean stereopsis was 85.8 ± 101.8 arcsec; 85 patients (85%) had good stereopsis (ie, ≥100 arcsec). Of the total patients, 12.5% shifted from exophoria to intermittent strabismus or exotropia at near vision, and near stereopsis decreased. Most of them had a preoperative near exophoria angle of more than 12 prism diopters. Conclusion: In bilaterally pseudophakic patients with a near exophoria angle of more than 12 prism diopters, we should be concerned about the possibility of variations in ocular deviation and stereopsis after cataract surgery.